Neosabellides lizae, a new species of Ampharetidae (Annelida) from Lizard Island, Great Barrier Reef, Australia - Alvestad, Tom; Budaeva, Nataliya (Zootaxa, 2015)
Neosabellides lizae, a new species of Ampharetidae, is described from the intertidal zone off Lizard Island, Great Barrier Reef, Queensland, Australia. The new species is referred to the genus Neosabellides based on the shape of the prostomium, three pairs of branchiae, 14 thoracic segments with notopodia, 12 thoracic uncinigerous segments, and the first two pairs of abdominal uncinigers of thoracic type. The new species differs from all known species of Neosabellides in having 14 abdominal uncinigerous segments.